Academic achievement among male and female students: the role of learning support and students' engagement - Mohd Yusoff, Hanita; Azman, Norzaini (Universiti Utara Malaysia Press, 2018)
Purpose – The study examines the relationship between students’ engagement, learning support and students’ achievement by gender.It also examines the extent to which student engagement plays a role in mediating the relationship between learning support and students’ achievement. Methodology - Cross sectional surveys were used to collect data on student engagement at school, their learning support and academic achievement. The sample consisted of 800 students, aged 16 (400 boys and 400 girls) from secondary schools in urban and rural areas in the district of Kuala Selangor, Malaysia. The Student Engagement Scale (Lam et al., 2009) was used for data collection. Pearson correlations and multiple regression were conducted to determine the relationship between variables. Structural equation modeling (SEM) was carried out to assess the role of student engagement in mediating the support of teachers, peers and parents, and students’ achievement by gender.Findings - The findings show a significant relationship between student engagement, learning support and academic achievement.Student engagement has a mediating influence on learning support and the academic achievement of both genders.Significance - The results of this study reinforces the theory on the role of learning support towards student achievement. Intervention programmes that increase the quality of learning support could be improved to enhance students’ academic engagement and outcomes.